SARS-CoV-2 serology in 4000 health care and administrative staff across seven sites in Lombardy, Italy - Maria Teresa Sandri (Nature Portfolio, 2021)
Abstract Lombardy is the Italian region most affected by COVID-19. We tested the presence of plasma anti-SARS-CoV-2 IgG antibodies in 3985 employees across 7 healthcare facilities in areas of Lombardy with different exposure to the SARS-CoV-2 epidemic. Subjects filled a questionnaire to self-report on COVID-19 symptoms, comorbidities, smoking, regular or remote working, and the exposure to COVID-infected individuals. We show that the number of individuals exposed to the virus depended on the geographical location of the facility, ranging between 3 and 43%, consistent with the spatial variation of COVID-19 incidence in Lombardy, and correlated with family interactions. We observed a higher prevalence of females than males positive for IgG, however the level of antibodies was similar, suggesting a comparable magnitude of the anti-spike antibody response. IgG positivity among smokers was lower (7.4% vs 13.5%) although without difference in IgG plasma levels. We observed 11.9% of IgG positive asymptomatic individuals and another 23.1% with one or two symptoms. Interestingly, among the IgG positive population, 81.2% of subjects with anosmia/dysgeusia and fever were SARS-CoV-2 infected, indicating that these symptoms are strongly associated to COVID-19. In conclusion, the frequency of IgG positivity and SARS-CoV-2 infection is dependent on the geographical exposure to the virus and primarily to family rather than hospital exposure.